NEED ANALYSIS IN THE DEVELOPMENT OF MINI RESEARCH-BASED GENERAL PHYSIOLOGY LEARNING SETS - Liska Berlian; Achmad Hufad; Maman Fathurrahman; Annisa Novianti Taufik; Siti Muhasitoh Mulyani (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
The general physiology course prepares prospective junior high school science teachers to master the content and science process skills. Skills used to acquire or apply science concepts, laws, theories including mental, physical and social skills are called science process skill. Science process skill is the basis for making rational and correct decisions about controversial issues. Science learning, including at the Junior High School level, should ideally not only be memorized knowledge but also a research process using science process skills, so that students are able to gain science knowledge from new phenomena in nature. To improve the students’ science process skills, the learning sets used by lecturers should be implemented effectively, so it is necessary to analyze the needs of learning sets. The research aims to explain the need analysis in the development of mini research-based general physiology learning sets. The research method used is a qualitative study with the data analysis technique of the Miles Huberman Model. This research was conducted in January 2022 at the Science Education Study Program, Faculty of Teacher Training and Education, University of Sultan Ageng Tirtayasa, Indonesia. Need analysis of learning sets includes needs in the aspects of students, concepts, assignments, and learning objectives. Needs analysis results are learning sets for general physiology based on mini-research suitable for improving the science process skills of prospective science teachers. Comprehensive and truly needs analysis can apply to the next stage of research and development. It can be concluded that the development of mini research-based general physiology learning sets should be conducted according to the findings of need analysis.